Effects of an educational technology application in the early detection of breast cancer - Anna Paula Sousa da Silva; Helanno Gomes Alexandre; Paulo César de Almeida; Lorena Barbosa Ximenes; Ana Fátima Carvalho Fernandes (Rev Rene)
Objective: to evaluate the effects of an educational technology application on the early detection of breast cancer. Methods: a quasi-experimental study of the Knowledge, Attitude and Practice survey type. The sample consisted of 294 women in two groups: Experimental Group and Control Group. Results: 9.5% of the participants of the experimental group before the educational intervention presented adequate knowledge and after the application of the technology there was an increase of 89.2%. Regarding the attitude, the experimental group in the early detection of breast cancer before the intervention had 69.9% and after the application was 89.2%. Only 61.2% of the participants presented adequate practice and, after applying the technology, this number rose to 93.7%. Conclusion: the knowledge, attitude, and practice of early breast cancer screening of women who participated in the applicability of the educational manual were different from those of women who did not participate.